Climate-Smart Livestock Interventions in West Africa: A Review - Amole, Tunde A.; Ayantunde, Augustine A. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
The livestock sector is one of the major contributors in agriculture, by some estimates contributing up to 18% of the global greenhouse gas (GHG) emissions. Of this, about one third is reported to be due to land use change associated with livestock production, another one third is nitrous oxide from manure and slurry management, and roughly 25% is attributed to methane emissions from ruminant digestion. Recent analysis suggests that developing world regions contribute about two thirds of the global emissions from ruminants, with sub- Saharan Africa a global hotspot for emissions intensities, largely due to low animal productivity, poor animal health and low quality feeds. These numbers suggest, therefore, that there are opportunities for easy gains to be made in terms of mitigation in the livestock sector, as improving feed resource use efficiencies would improve livestock productivity as well as reduce emissions per unit of product. In this context, climate-smart agricultural practices are necessary in the West Africa region and in sub-Saharan Africa in general. Climate-Smart Agriculture (CSA) is an approach that provides a conceptual basis for assessing the effectiveness of agricultural practice change to support food security under climate change. This review focuses on livestock-related CSA options in West Africa looking at herd management, feed, grazing management, animal breeding strategies, manure management, and policy options.